Zwischen geistiger Erneuerung und Restauration - Stifter, CHristian H. (Böhlau, 2021)
The book discusses the origins and the formation of U.S. reorientation strategies for post-war democratization and its implementation in the aftermath of World War II, exemplified by case studies of university and academic reconstruction in Austria in the years from 1945 to 1955. The study illustrates and analyzes both the changes and the specific implementations of U.S. reorientation strategies, starting with the war years and continuing up to U.S. propaganda strategies at the outbreak of the Cold War and its subsequent ramifications of post-war-democratization. After the end of World War II, the initial civil intent of U.S. reorientation was to foster a sustainable peacebuilding process by means of intellectual disarmament and a set of long-term democratization measures. The focus of reorientation narrowed first to the limited repertoire of educational and academic policy before ultimately becoming a propaganda instrument of the Cold War.